A Constitutional Analysis of Active-Duty TNI Personnel in Ministries and State Institutions under Law No. 3 of 2025 - Agung Fakhruzy; Wardatul Laili (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The amendment to Law Number 34 of 2004 concerning the Indonesian National Armed Forces through Law Number 3 of 2025 has generated debate over the constitutionality of expanding the positions that may be held by active-duty TNI personnel in ministries and state institutions. This amendment warrants examination because it potentially affects the principles of the rule of law, constitutional democracy, civilian supremacy, and the professionalism of the TNI as a state instrument in the field of national defense. This study aims to analyze the compatibility of the legal regulation governing the involvement of active-duty TNI personnel in positions within ministries and state institutions with the 1945 Constitution of the Republic of Indonesia and the principles of a democratic rule-of-law state. This study employs normative legal research using a statutory approach and a conceptual approach. The primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, Law Number 34 of 2004, Law Number 3 of 2025, and relevant decisions of the Constitutional Court. Secondary legal materials include books, scholarly journals, and legal doctrines, while tertiary legal materials consist of legal dictionaries. Legal materials were collected through documentary research by identifying, inventorying, and examining relevant legislation, judicial decisions, and academic literature. The legal materials were analyzed qualitatively through grammatical, systematic, and constitutional interpretation. The findings indicate that the amendment to Article 47 expands the scope of positions that may be occupied by active-duty TNI personnel from 10 to 14 ministries and state institutions. Although the provision remains limitative, the expansion potentially broadens the military's role in the civilian governmental sphere and creates tension with the principle of civilian supremacy and the spirit of the Reform Era. Therefore, strict constitutional interpretation is necessary to ensure that the implementation of the provision preserves the professionalism of the TNI and does not revive the practice of military dual function